2017
DOI: 10.1111/lapo.12076
|View full text |Cite
|
Sign up to set email alerts
|

The Right to Be Racist in College: Racist Speech, White Institutional Space, and the First Amendment

Abstract: Throughout the post-civil rights era, colleges and universities across the United States have periodically experienced explicitly racist incidents on their campuses. From the hurling of racial slurs at students of color, to the hanging of nooses on campus, to students donning Ku Klux Klan outfits or throwing "ghetto" parties that caricaturize communities of color, these incidents challenge the notion that modern racism has changed to a more subtle form, referred to as colorblind racism. We place these incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 18 publications
2
48
0
Order By: Relevance
“…Here the concept of white institutional space is useful for understanding the impact the social contexts of PWIs have on processes of black authenticity. White institutional space helps to explain the patterns and mechanisms of the production and reproduction of racial privilege and power in various institutional contexts (Moore 2008; Moore and Bell 2017). This theoretical concept “illuminates the entrenchment of white privilege in institutional contexts as well as the white normativity that justifies and reproduces that white privilege” (Moore and Bell 2017:102).…”
Section: Social Context and The Precarity Of Black Authenticitymentioning
confidence: 99%
“…Here the concept of white institutional space is useful for understanding the impact the social contexts of PWIs have on processes of black authenticity. White institutional space helps to explain the patterns and mechanisms of the production and reproduction of racial privilege and power in various institutional contexts (Moore 2008; Moore and Bell 2017). This theoretical concept “illuminates the entrenchment of white privilege in institutional contexts as well as the white normativity that justifies and reproduces that white privilege” (Moore and Bell 2017:102).…”
Section: Social Context and The Precarity Of Black Authenticitymentioning
confidence: 99%
“…Perhaps it is time to "explore the being of the university anew and with a focus on the dimensions of the university that are not linked to higher education and, therefore, only occasionally have overlaps with teachers, students, and a formalized curriculum". 64 In becoming sensitive to the energy in alien ecologies, it might be feared that higher education might drift away from the societal, cultural, and political domains, but rather to the contrary it gathers, and it brings itself into play in new, surprising, and strange ways.…”
Section: Nothingness and The Move Towards Alien Ecologiesmentioning
confidence: 99%
“…63 This point is further emphasized by Moore and Bell who explored an interlocking and reciprocal relationship between overt acts of racism, colorblind racism, and the persistence of white institutional spaces. 64 By rejecting overt racism, institutions rhetorically define what "counts" as racism, situate themselves as nonracist, and camouflage continued participation in racialized institutional practices and structures. 65 Thus, the statements by the UA and Emory, which emphasize that the chalking messages "have no place on our campus community," serve to delink the acts from the culture of the campus, and in doing so reaffirm the persistence of colorblind racist ideologies.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Ben had remarked. Moore and Bell (2017) suggested that there is a symbiotic relationship between overt acts of racism on campuses and more subtle, colourblind racism, a relationship that serves to reproduce the space of higher education as white space, reinscribing and reinforcing white supremacy. For example, even as administrators denounce acts of racism, this denouncement erases other, more subtle forms of racism, (re)producing campus spaces as racist and perpetuating white supremacy.…”
Section: Rightmentioning
confidence: 99%